Metabolic Dysfunction–Associated Fatty Liver Disease (MAFLD) and Thyroid Function in Childhood Obesity: A Vicious Circle? - Valeria Calcaterra; Irene Degrassi; Silvia Taranto; Cecilia Porro; Alice Bianchi; Sara L’assainato; Giustino Simone Silvestro; Antonia Quatrale; Gianvincenzo Zuccotti (Children, 2024)
Metabolic dysfunction–associated fatty liver disease (MAFLD) is a multisystem disorder characterized by the presence of fatty liver degeneration associated with excess adiposity or prediabetes/type 2 diabetes or metabolic dysregulation. An intricate relationship between the liver and thyroid has been reported in both health and disease. Simultaneously, there is a strong correlation between obesity and both MAFLD and thyroid dysfunction. In this narrative review, we highlighted the relationship between MAFLD and thyroid function in children and adolescents with obesity in order to explore how thyroid hormones (THs) act as predisposing factors in the onset, progression, and sustainability of MAFLD. THs are integral to the intricate balance of metabolic activities, ensuring energy homeostasis, and are indispensable for growth and development. Regarding liver homeostasis, THs have been suggested to interact with liver lipid homeostasis through a series of processes, including stimulating the entry of free fatty acids into the liver for esterification into triglycerides and increasing mitochondrial β-oxidation of fatty acids to impact hepatic lipid accumulation. The literature supports a correlation between MAFLD and obesity, THs and obesity, and MAFLD and THs; however, results in the pediatric population are very limited. Even though the underlying pathogenic mechanism involved in the relationship between MAFLD and thyroid function remains not fully elucidated, the role of THs as predisposing factors of MAFLD could be postulated. A potential vicious circle among these three conditions cannot be excluded. Identifying novel elements that may contribute to MAFLD could offer a practical approach to assessing children at risk of developing the condition.